Analisis Pelaksanaan Mata Kuliah Pendidikan Pancasila di Perguruan Tinggi - Prasetyo, Danang (RONTAL: Jurnal Keilmuan Pancasila dan Kewarganegaraan, 2019)
This study aims to determine (1) the policy of implementing the Pancasila Education course in Higher Education, (2) the Pancasila Education teaching material, (3) the supporting resources of the Pancasila Education course, (4) The solution to the implementation of the Pancasila Education course. The study and analysis of Pancasila education in Higher Education is done by emphasizing on three important aspects that have not been much of concern to researchers, observers, and educators. First, the policy aspects related to Pancasila education in Higher Education which undergo various phases of change both through legislative policies, ministerial regulations, and institutional policies carried out by Universities in Indonesia. Second, the teaching material or material aspects used by the lecturers of Pancasila Education courses. Third, aspects of teaching resources or lecturers who teach Pancasila Education courses. The approach taken in this study emphasizes the approach to library research. The method of collecting data is obtained through an inventory of data or documents, then examines data or documents in the form of product policies, legislation, books, scientific journals, newspaper articles, and documents relating to the topic of this study. The results of this study indicate that (1) the Pancasila Education policy in Higher Education must be strengthened again by strengthening the teaching capacity of Pancasila education, and monitoring the consistency of policies applied in each tertiary institution is carried out regularly, (2) standardizing teaching material materials nationally because At present there are many cases of misunderstanding and interpretation of the Pancasila, (3) there needs to be special rules or standardization relating to the recruitment of lecturers of Pancasila Education courses in Higher Education. Keywords:  policy, pancasila education, higher education